Impact Of Climate Change On Cognitive Aspect And Income Of Marn Farmers In Marginal Area In Lombok Timur District - Muhammad Joni Iskandar; Adnan Putra Pratama; Andi Lisnawati (UNIVED Press, Dehasen University Bengkulu, 2023)
Climate change is a phenomenon that farmers do not want to exist because the production risk it creates is quite high. Given that the ability of farmers in anticipation is still minimal with limited information and knowledge so that the potential for crop failure is large. The purpose of this study is to estimate the impact of climate change on the cognitive aspects and income of corn farmers in marginal areas. The research location was determined purposively in Jerowaru District. The research sample of 30 was determined by census in the Temodo Lestari farmer group. Estimation of the cognitive aspects uses the EPIC model with the Likerts Summated Rating Scale (LSRS) while income is estimated using the concept of total revenue minus the total cost while running a corn farming business. The results showed that more than 60 percent of farmers know about climate change and the risks it poses. While the climate change adaptation strategy for the majority of farmers has not implemented it as a result of more than 30 percent of farmers still lack information related to climate change. The income of corn farmers due to climate change is more than 40 million per hectare.